(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
A paleochristian or protobizantyne double half-column pillar from Gortys is object of epigraphic interest because both its bedding and its resting surfaces support one letter of the Greek alphabet (rho and phi). Paleographically, the two letters under discussion have no comparison in the Gortynian corpus. Probably our epigraphic documents have to be ascribed to the very wide epigraphic category of masons’s marks, and they could particularly fall within the subgroup of fitters’ marks.